Deciphering the crime-terror Nexus: an empirical analysis of the structural characteristics of terrorists in Narco-terror networks - Ünal, Mustafa Cosar (Crime, law and social change, 2020)
By using Social Network Analysis (SNA) technique, this study analyzes the structural characteristics of five PKK related narco-terror networks. It examines the roles and positions occupied by PKK members to uncover the nature of the terrorist nexus itself and analyzes structural characteristics to identify these networks’ prioritization between security and efficiency. This study finds that terrorists have key roles in narco-terror networks, i.e., leaders, managers, or drug suppliers. They take powerful and central positions in either controlling central hubs (exerting authority) or bridging separate subgroups (acting as a gateway) constituting the core parts of networks. Further, this study finds that despite terrorists’ dominating role and positions in control and coordination of information and resources, narco-terror networks reveal more reliance on efficiency than security. In general, these networks tend to be clustered into dense subgroups that are attached to networks’ cores, reflecting relatively denser and centralized structures with short average paths. Yet, networks have core(s) whereby key players act predominantly in these cores rather than on peripheries. Notwithstanding the dominance of terrorist members, narco-terror networks seem to focus more on efficiency, and the terrorist nexus in such networks does not appear to make these networks more security-driven. This study asserts that the nature of activity (i.e., crime for material incentive) determines how offenders behave and how covert networks are structured.